Cultural Interactions During a One – Year Polish Language Course. Congolese and Angolan Students – A Case Study - Koniuk, Michalina (Activation – innovation – acculturation. (Glotto)didactics and the migration crisis, 2024)
This article is devoted to the cultural interactions taking place during a one-year intensive Polish language course organised at the Nicolaus Copernicus University in Toruń in two African groups: - Congolese and Angolan. Observing the behaviour of the students in these groups, over such a long period of time, made it possible to identify manifestations of cultural differences between the two groups of learners. The division, dictated by organisational considerations, has also made it possible to look at cultural interactions within the groups. The aim of this article is to present the differences and similarities between Congolese and Angolan culture and to present teaching problems against this background, supported by examples from the learner’s work.